Manusia dan Alam Dalam Bingkai Harmoni: Menggali Konsep Pendidikan Organik Ki Hajar Dewantara - Sumiati, Teti; Kartimi, Kartimi; Rahtikawati, Yayan (Indonesian Journal of Education and Social Sciences, 2025)
The development of technology makes human life easier, but on the other hand, technology has an impact on the strained relationship between humans and mental health problems. Education has an important role in building a better civilization. In the midst of its problems, organic education pioneered by Ki Hajar Dewantara is an alternative education that can harmonize the relationship between humans and nature. Returning human nature as a servant and caliph on earth. . This study aims to explain the Islamic view on the relationship between humans and nature and its relevance to the concept of organic education popularized by Ki Hajar Dewantara considering that the approach used is more holistic, not only involving intellectual development, but also combining ecological and spiritual awareness in human life. The research method used is the literature study method. The conclusion of this study is that humans are part of a larger system, namely the universe and are interdependent on each other. Organic education is a promising alternative to bring humans back into harmony with the universe. By integrating ecological, social, and spiritual values ​​into the education curriculum, we can form a generation that is more aware and responsible for the sustainability of life on this earth.